Dialektika Transgender dan Hadis Nabi: Analisis Semiotika terhadap Hadis Riwayat Bukhari No. 5885 - Lubis, Manahara Alamsyah; Harun, Amrullah (UIN Sultan Syarif Kasim Riau, 2025)
The transgender phenomenon is a social reality that is becoming increasingly evident in contemporary society. From the perspective of hadith, behaviors that mimic the opposite gender are regarded as prohibited. This study aims to examine the hadith that prohibits the imitation of the opposite gender within the context of the transgender phenomenon, utilizing Umberto Eco’s semiotic communication approach. The research questions include: What are the general and Islamic views on transgender issues? How does the dialectic between the hadith regarding transgender and Eco’s semiotic theory manifest? How is this theory applied to the hadith that prohibits dressing like the opposite gender? This study employs qualitative methods, drawing on literature sources, with the primary hadith sourced from al-Bukhari No. 5885, and theoretical insights from the Theory of Semiotics. The analysis is conducted by adapting the elements of semiotic communication: source, transmitter, signal I, channel, signal II, receiver, message II, and destination, with the addition of message I to capture the intention of the Prophet as the direct transmitter. The results indicate that the Prophet serves as the source, the Prophet’s sayings represent message I, the narrators act as transmitters, oral transmission functions as signal I, hadith collections serve as the channel, the written text represents signal II, the Muslim community acts as the receiver, the hadith text constitutes message II, and the understanding of meaning serves as the destination. The hadith explicitly prohibits Muslims from deliberately imitating the opposite gender in various aspects, including clothing, adornments, speech style, and mannerisms. Intentional engagement in transgender behavior is categorized as condemned conduct. However, for individuals with innate tendencies, Islam underscores the importance of self-adjustment in accordance with fitrah, as taught in Islamic teachings.Abstrak: Fenomena transgender merupakan realitas sosial yang semakin nyata dalam masyarakat modern. Dalam perspektif hadis, perilaku menyerupai lawan jenis dipandang sebagai sesuatu yang terlarang. Penelitian ini bertujuan mengkaji hadis larangan menyerupai lawan jenis dalam konteks fenomena transgender dengan menggunakan pendekatan semiotika komunikasi Umberto Eco. Rumusan masalah mencakup: bagaimana pandangan umum dan Islam terhadap transgender, bagaimana dialektika antara hadis tentang transgender dan teori semiotika Eco, serta bagaimana penerapan teori tersebut terhadap hadis larangan berpakaian seperti lawan jenis. Penelitian ini menggunakan metode kualitatif dengan memanfaatkan sumber-sumber kepustakaan, sumber utama hadis riwayat al-Bukhari No. 5885 dan teori dari A Theory of Semiotics. Analisis dilakukan dengan mengadaptasi unsur-unsur komunikasi semiotik: source, transmitter, signal I, channel, signal II, receiver, message II,dan destination, serta menambahkan message I untuk menangkap intensi makna Nabi sebagai penyampai langsung. Hasil analisis menunjukkan bahwa Nabi merupakan sumber (source), sabda Nabi sebagai message I, perawi sebagai transmitter, penyampaian lisan sebagai signal I, kitab hadis sebagai channel, redaksi tertulis sebagai signal II, umat sebagai receiver, redaksi hadis sebagai message II, dan pemahaman makna sebagai destination. Hadis tersebut secara eksplisit melarang umat Islam untuk menyerupai lawan jenis dalam aspek pakaian, perhiasan, gaya bicara, dan cara berjalan secara sengaja. Fenomena transgender yang dilakukan secara sadar masuk dalam kategori perilaku yang dilaknat. Namun, bagi individu yang memiliki kecenderungan bawaan, Islam menekankan pentingnya penyesuaian diri sesuai fitrah menurut ajaran Islam.